(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Anal fistula (fistulous paraproctitis) is a chronic anorectal condition characterized by an abnormal tract connecting the anal canal or rectum with the perianal skin. It significantly impairs patients’ quality of life due to pain, discharge, and risk of recurrence. This review provides a comprehensive analysis of classification systems, diagnostic approaches, and both conventional and emerging treatment strategies for anal fistulas. Modern imaging techniques, including MRI and endoanal ultrasound, have improved preoperative assessment and surgical planning. Surgical management remains the cornerstone of treatment, with sphincter-preserving approaches such as LIFT, VAAFT, and advancement flaps aiming to balance healing and continence preservation. In this article, we summarized and critically analyzed current literature on the etiology, diagnostic methods, and management options of anal fistula, emphasizing the shift from purely surgical to regenerative and minimally invasive strategies. We also outlined future perspectives integrating imaging precision with biological repair techniques.